Studi Pengaruh Pemberian Tumis Daun Pepaya (Carica papaya L.) terhadap Produksi Asi dan Peningkatan Berat Badan Bayi - Rizki Novi Arnely Putri; Dewi Kurniati; Shinta Novelia (Poltekkes Kemenkes Kendari, 2020)
Breastfeeding that is not satisfactory causes stunted growth and development of the baby and one of the reasons that cause stress to breast-feeding mothers. One approach to coping with this is to eat papaya leaves containing lactagogues in breastfeeding mothers that are useful for helping to smooth out breastfeeding. This research has proven the influence of hopped papaya leaves on the production of breast milk in nursing mothers. The nature of the study was a quasi-experiment in two groups (before and after therapy). Thirty mothers who were breast-feeding and split into two intervention groups and a control group were involved in this investigation at the Permata Hati Clinic. The studies carried out are normality tests (Shapiro-Wilk), non-parametric descriptive analyzes, and frequency distribution tests for obtained data (Wilcoxon Signed-Rank Test). There was a substantial difference (p = 0.000) in treatment before and after the use of sautéed papaya leaves in the milk production of nursing mothers, so it can be inferred that giving sautéed papaya leaves may increase milk production in nursing mothers. This study is expected to form the basis for proposals so that midwives can provide nursing mothers with education about the benefits of sautéed papaya leaves and how they can be processed to improve the smooth production of breast milk.